2015
DOI: 10.1007/s10526-015-9693-0
|View full text |Cite
|
Sign up to set email alerts
|

Weeds within willow short-rotation coppices alter the arthropod community and improve biological control of the blue willow beetle

Abstract: Outbreaks of the blue willow beetle Phratora vulgatissima (L.) (Coleoptera: Chrysomelidae) threaten the yield of willow plantations that rely on biological control by natural enemies. Here we show that weed presence increases herbivore and predator/parasitoid diversity on willow shoots and causes increased predation on P. vulgatissima eggs compared to shoots within plots without weeds. We argue that, in addition to higher abundance, the community shift in favour of egg consumers and additive predator effects c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…However, identifying the mechanisms involved in these changes is complex and requires a comprehensive approach [ 38 ]. In the first scenario, the presence of non-crop plants in the agroecosystem likely diversified microhabitats, allows the recruitment and conservation of species with different dietary, ecological and habitat requirements mainly due to the increasing availability of floral resources, which results in a diversified community [ 39 41 ]. The increasing complexity in the lettuce crop, arising from flowers, nectar and shelter, partially explains the higher richness and abundance in lettuce recorded during the marigold flowering stages [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, identifying the mechanisms involved in these changes is complex and requires a comprehensive approach [ 38 ]. In the first scenario, the presence of non-crop plants in the agroecosystem likely diversified microhabitats, allows the recruitment and conservation of species with different dietary, ecological and habitat requirements mainly due to the increasing availability of floral resources, which results in a diversified community [ 39 41 ]. The increasing complexity in the lettuce crop, arising from flowers, nectar and shelter, partially explains the higher richness and abundance in lettuce recorded during the marigold flowering stages [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is probably difficult to detect whether predation risk would be lower on specific plant genotypes (Stephan, Albertsson, et al, 2016), we did find some preliminary evidence. Certainly, the influence of retaining eggs or delaying oviposition still needs to be evaluated as many other factors, including habitat heterogeneity (Andersson, Löfstedt, & Hambäck, 2013), valuing an individual's own performance higher than that of its offspring (Mayhew, 2001), and higher predation risk on otherwise suitable hosts (Egusa, Nishida, Sawada, & Fujisaki, 2008), may override this positive effect on fitness.…”
Section: Discussionmentioning
confidence: 64%
“…We have yet to determine the real contributions of plant genotype-mediated changes to nonconsumptive effects and the ultimate outcome to the plant. In many biological control strategies, pest density is estimated by counting the individuals or assessing the damage and relating it to the predator/parasitoid density/diversity under consideration of spillover and dilution effects (Andow, 1991;Stephan, Albertsson, Wang, & Porcel, 2016). However, after accounting for these, care should be taken to link any desired pest control to consumption directly, as there may be a nonconsumptive component.…”
Section: Discussionmentioning
confidence: 99%
“…Landis et al (2000) showed that the presence of flowering plants in agroecosystems is a conceptually simple mean to increase densities of predators and parasitoids, since several natural enemies use pollen and/or nectar as alternative food. However, increased abundance of predators and parasitoids to be of benefit for biological control, should translate into increased predation (Stephan et al, 2016). Studies on mirids have shown that habitat management could lead to higher predator abundance and as a result to higher prey consumption (Perdikis et al, 2011;Ingegno et al, 2017).…”
Section: Discussionmentioning
confidence: 99%